Precedent Noun Fiction In Shavkat Rahman's Poetry (Eurasian Journal of Humanities and Social Sciences, 2024)
This article shows the linguistically rich possibilities of the Uzbek language through the linguistic analysis of poetonyms used in the poetry of the poet Shavkat Rahman.